Effect of Nigella sativa fixed and essential oils on antioxidant status, hepatic enzymes, and immunity in streptozotocin induced diabetes mellitus - Sultan, Muhammad Tauseef; Butt, Masood Sadiq; Karim, Roselina; Iqbal, Shahzad Zafar; Ahmad, Shakeel; Zia-Ul-Haq, Muhammad; Aliberti, Luigi; Ahmad, Atif Nisar; De Feo, Vincenzo (BioMed Central, 2014)
Background: Nigella sativa fixed (NSFO) and essential (NSEO) oils have been used to treat diabetes mellitus and its complications. Present study was undertaken to explore and validate these folkloric uses. Methods: Sprague dawley rats having streptozotocin (STZ) induced diabetes mellitus were used to assess the role of NSFO and NSEO in the management of diabetes complications. Parameters investigated were antioxidant potential, oxidative stress, and the immunity by in vivo experiments. Results: The results indicated that STZ decreased the glutathione contents (25.72%), while NSFO and NSEO increased the trait significantly (P < 0.05). Experimental diets increased the tocopherol contents (P < 0.01) and enhanced the expression of hepatic enzymes (P < 0.01). Correlation matrix further indicated that antioxidant potential is positively associated (P < 0.05) responsible for the modulation of hepatic enzymes and the decrease of the nitric oxide production thus controlling the diabetes complications. Conclusions: Overall, results of present study supported the traditional use of N. sativa and its derived products as a treatment for hyperglycemia and allied abnormalities. Moreover, N. sativa fixed and essential oils significantly ameliorate free radicals and improve antioxidant capacity thus reducing the risk of diabetic complications.